THE WTO AND THE CHALLENGES OF GLOBAL TRADE : RISKS AND OPPORTUNITIES IN THE CURRENT LANDSCAPE - Urrea Salazar, Martín Jesús (International Journal of Law in Changing World, 2025)
No one can doubt today the close relationship between international trade and development. In this regard, the existence of a universal multilateral trading system—based on rules, open, non-discriminatory, and equitable—constitutes one of the objectives underpinning the Sustainable Development Goals adopted within the United Nations framework. From the perspective of commercial actors, the impact of the rules derived from the World Trade Organization on their commercial activities becomes essential. The pursuit of legal certainty is essential in business, particularly in international trade. In this regard, one can distinguish between a public-legal framework and a private dimension, the latter being “regulated” by the rules of Private International Law. __________ LA OMC Y LOS RETOS DEL COMERCIO MUNDIAL: RIESGOS Y OPORTUNIDADES EN EL PANORAMA ACTUAL Hoy en día, nadie puede dudar de la estrecha relación entre el comercio internacional y el desarrollo. En este sentido, la existencia de un sistema multilateral de comercio universal —basado en normas, abierto, no discriminatorio y equitativo— constituye uno de los objetivos que sustentan los Objetivos de Desarrollo Sostenible adoptados en el marco de las Naciones Unidas. Desde la perspectiva de los actores comerciales, el impacto de las normas derivadas de la Organización Mundial del Comercio en sus actividades comerciales resulta esencial. La búsqueda de la seguridad jurídica es esencial en los negocios, en particular en el comercio internacional. En este sentido, se puede distinguir entre un marco jurídico público y una dimensión privada, esta última regulada por las normas del Derecho Internacional Privado. __________ 世界贸易组织与全球贸易的挑战：当前形势下的风险与机遇 如今，国际贸易与发展之间的密切关系毋庸置疑。为此，建立一个基于规则、开放、非歧视和公平的普遍多边贸易体系，是联合国框架下通过的可持续发展目标的核心目标之一。从商业主体的角度来看，世界贸易组织规则对其商业活动的影响至关重要。追求法律确定性在商业活动中，尤其是在国际贸易中，至关重要。在这方面，我们可以区分公共法律框架和私人层面，后者受国际私法规则的“规制”。